Shear performance of ultra-high performance concrete multi-keyed epoxy joints in precast segmental bridges. (December 2022) - Chen, Liang; Yan, Jing; Xiang, Nailiang; Zhong, Jian
Abstract: Ultra-high performance concrete (UHPC) is increasingly used as a new material in precast segmental bridges to strengthen the connection between structural components such as joints. In this study, the shear behaviour and capacity of UHPC multi-keyed epoxy joints in segmental bridges are investigated. Push-off tests are conducted on scaled joint specimens designed with different parameters including joint type, confining stress, number of shear keys, and distance between shear keys. Experimental results are used to calibrate and generate three-dimensional finite element (FE) models of UHPC multi-keyed epoxy joints. Using the FE models, the uneven distribution of shear keys of the multi-keyed epoxy joints is investigated. The equations in the codes of AASHTO and JSCE cannot provide an accurate prediction of the shear capacities of multi-keyed UHPC epoxy joints, thus improved predictive equations that incorporate the effect of uneven distribution of shear stress in multi-keyed epoxy joints are proposed. The accuracy of the proposed equations is well validated against experimental and numerical results.